Physical distancing and non-respiratory notifiable diseases in the Northern Territory, March-May 2020 - Xie, Ouli; Markey, Peter G; Draper, Anthony D K; Krause, Vicki L (Communicable Diseases Intelligence, 2020)
Strict physical distancing measures and border controls have been introduced in the Northern Territory (NT), and across Australia, to reduce the spread of coronavirus disease 2019 (COVID-19). These measures have been associated with reduced incidence of other respiratory illnesses such as influenza. It is currently unclear what effect these measures have on non-respiratory communicable diseases. The incidence of notifiable non-respiratory communicable diseases within the NT, from 15 March to 15 May 2020, the period of most restrictive physical distancing, was monitored and is here compared with two control periods: (i) the 4 months immediately prior and (ii) the same two-month period from the preceding 5 years. During the study period, there was a decline in incidence of communicable enteric illnesses, particularly in shigellosis and rotavirus where person-to-person spread is the main transmission route. There was an increase in chlamydial conjunctivitis in areas with endemic trachoma, which is under further investigation. There was no observed increase in conditions associated with crowding, such as those related to group A streptococcal infection.